IMPLEMENTATION OF TRS-398 PROTOCOL IN ROUTINE CALIBRATION OF LINAC BY DETERMINATION OF SLAB PHANTOM ON WATER PHANTOM CORRECTION FACTOR - Azizallah Fauzi; Fitrotun Aliyah; Darmawati Darmawati (Program Studi Fisika Universitas Negeri Jakarta, 2022)
The water phantom is used for LINAC calibration to measure absorbed dose radiation. Practically, it requires a long preparation time and is considered less efficient. To increase efficiency, the medical physics team in a hospital uses slab phantom as the calibration tool. Consequently, the correction factor is crucial to define the equivalence of the absorbed doses resulted from slab phantom. The absorbed dose measurement was performed according to the IAEA TRS-398 dosimetry protocol with a cylindrical ionization chamber detector for 6 MV photon beam and electron beams from Elekta Synergy Platform 154029 LINAC with 6 MeV, 8 MeV, 10 MeV, and 12 MeV energy variations. The field size for slab and water phantom is 30 cm x 30 cm x 30 cm. Based on the TRS-398 protocol, the correction factor of the slab phantom calculated based on absolute dosimetry for 6 MV photons beam, the electron beam of 6 MeV, 8 MeV, 10 MeV, and 12 MeV are 1.0018; 0.9995; 0.9979; 1.0041 and 1.0068, respectively. As a result, the absorbed dose radiation measured by the calibrated slab phantom using the resulted correction factor has an equivalent amount to the water phantom.